Research Funding for Pain in Canada - Mary E Lynch; Donald Schopflocher; Paul Taenzer; Caitlin Sinclair (Pain Research and Management)
Chronic pain is an escalating public health problem. There are inadequate resources to assist patients suffering with pain in Canada. Therefore, it is important that research examining novel and appropriate treatment for chronic pain is conducted. To determine the current level of research funding for pain in Canada, the Canadian Pain Society conducted a survey. Of 79 active researchers performing pain-related studies, 65 received funding in the past five years amounting to a total of approximately $80.9 million. This is less than 1% of the total funding from the Canadian Institutes of Health Research and 0.25% of the total funding for health research.